Comparison Effect of Resin and Catalyst Against Fiberglass-Composite Tensile Strength Polyester For Ship Building Materials (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2020)
The use of fiberglass-based composites is often found in shipbuilding. However, the use of composites in the shipbuilding process does not yet have clear and standard quality standards regarding the ratio between the amount of resin and catalyst used. Meanwhile, the amount of use of resin and  atalyst has an influence on the strength of the fiber-reinforced composite. This study aims to determine the effect of the amount of catalyst mixed into the resin on the tensile strength of fiberglass-polyester composites. The method used in this study is an xperimental method that uses a tensile testing machine by varying the amount of catalyst in the resin from 0.5% to 2%. In this study, the results showed that composites with a catalyst amount of 0.5% had a tensile strength value of 4.85 kgf/mm2, elongation of 2.43% and elastic modulus of 2.26 kgf/mm2. Composites with a catalyst amount of 1% had a tensile strength value of 5.02 kgf/mm2, longation of 1.71% and elastic modulus of 2.96 kgf/mm2. Composites with a catalyst amount of 1.5% had a tensile strength value of 5.49 kgf/mm2, longation of 1.97% and elastic modulus of 3.07 kgf/mm2. Composites with a catalyst amount of 2% had a tensile strength value of 4.97 kgf/mm2, longation of 1.62% and elastic modulus of 3.11 kgf/mm2. The tensile strength of fiberglass-polyester composites has increased in the amount of catalyst 0.5 to 1.5% and has decreased in the amount of catalyst 2%. The highest value of tensile strength is in composites with a composition of 100% resin and 1.5% catalyst.
Keywords: Fiberglass, Catalyst, Tensile Strength, Composite.